Penyuluhan Program STBM - Pengelolaan Air Minum Rumah Tangga di Puskesmas Rumbai Pesisir - Kota Pekanbaru di Masa Covid-19 - Herniwanti, Herniwanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
STBM (Community-Based Total Sanitation) pillar 3 is the Management of Drinking Water and Household Food (PAM-RT) which is an important thing to pay attention to during the Covid-19 pandemic and also in stunting prevention. The purpose of this activity is to be able to improve the implementation of STBM for household-scale Drinking Water Management for STMB Cadres in the Rumbai Pesisir Health Center which is a target area of ​​community service activities for the second period of 2020 from a lecturer in Master of Public Health, Hang Tuah University Pekanbaru as an implementation Tri Dharma college. The method of this Community Service Activity is through socialization and triggering to 34 STBM cadres from 4 kelurahan and related parties in the Puskesmas and Kec. Rumbai Pesisir in February 2021. The results of socialization and discussions with cadres stated that generally the problem for drinking water is that they consume gallons of drinking water and also use drinking water that is cooked by themselves from PDAM and also wells whose quality has not been tested for quality standards so that they require supervision and also outreach from the health department. STBM, District and Community Health Center cadres need support from academics through community service activities to provide input and evaluation so that the program remains enthusiastic about running, especially during the Covid 19 period and also stunting prevention.